Chemoselective Transfer Hydrogenation of Aldehydes with HCOONH4 Catalyzed by RuCl(CNNPh)(PP) Pincer Complexes. Issue 20 (21st September 2016) - Baldino, Salvatore; Facchetti, Sarah; Nedden, Hans Günter; Zanotti‐Gerosa, Antonio; Baratta, Walter
Abstract: Aldehydes were chemoselectively reduced to primary alcohols by using HCOONH4 as the hydrogen donor through transfer hydrogenation catalyzed by benzo[ h ]quinoline pincer complexes RuCl(CNN Ph )(PP) at substrate to catalyst molar ratios of 2000 to 20 000. This practical reaction performed with aldehydes of commercial‐grade purity in a water/toluene biphasic system afforded alcohols without the formation of condensation or amination side products. Abstract : A little pinch : Commercial‐grade aldehydes can be reduced to alcohols through transfer hydrogenation with ammonium formate as the hydrogen donor and catalyzed by benzo[ h ]quinoline pincer ruthenium complexes without the formation of condensation or amination side products.